FRI0204 Effect of Tocilizumab Treatment on QTc Interval in Patients with Rheumatoid Arthritis without Cardiac Symptoms. (15th July 2016) - Yokoe, I.; Kobayashi, H.; Nishiwaki, A.; Sugiyama, K.; Nagasawa, Y.; Karasawa, H.; Iwata, M.; Nozaki, T.; Ikumi, N.; Inomata, H.; Shiraiwa, H.; Kitamura, N.; et al.
Abstract : Background: Individuals with rheumatoid arthritis (RA) are at a 2-fold increased risk of sudden death compared with age- and gender-matched controls without RA. Although mechanisms underlying the increased risk are yet unclear, evidence indicates effects of systemic inflammation on ventricular repolarization. Accordingly, corrected QT (QTc) interval prolongation is more frequent in patients with RA than in those without RA. A previous pilot study reported that tocilizumab (TCZ) normalizes the QTc interval by dampening systemic inflammation. Objectives: Our study prospectively evaluates TCZ treatment effects on the QTc interval of patients with RA without cardiac symptoms and explores the association between this QTc interval and RA disease activity and severity measures. Methods: This prospective interventional study was conducted between March 2012 and August 2015 at the Itabashi Chuo Medical center. Patients who fulfilled the American College of Rheumatology (ACR) RA classification criteria or the 2010 ACR/ European League against Rheumatism RA criteria were included. Exclusion criteria included diabetes, history of cardiovascular events, hypertension (systolic blood pressure (BP) >140 mm Hg and/or diastolic BP >90 mm Hg), dyslipidemia (LDL cholesterol levels >140 mg/dL, HDL cholesterol level <40 mg/dL, or triglyceride level >150 mg/dL), cardiomyopathy, renal disease, and current atrial fibrillation. Age- and gender-matched healthy controls without any cardiac symptoms were selected. Patients with active RA with inadequate clinical response to methotrexate (MTX) were administered tocilizumab (TCZ 8 mg/kg IV every 4 weeks or 162 mg SC biweekly). Electrocardiography and clinical and biological monitoring were performed at baseline and 24 weeks after TCZ treatment in patients with RA. Results: Ninety patients with RA (mean age: 56.4±10.4 yers; 85% female) and 40 age and gender matched healthy controls (mean age 55.6±3.4 years; 86% female) were included, of which 20% and 13% of RA patients received antihypertensive and antihyperlipidemia therapy, respectively. No significant differences were observed in mean Framingham 10 scores between healthy controls and patients with RA at baseline. The 24-week Simplified Disease Activity Index scores were significantly lower than those at baseline. Using previously established cutoffs (440 ms), we identified 8 (10%) patients with abnormal QTc interval prolongation. However, QTc intervals at baseline were higher in patients with RA than in controls (mean SD 420.3 ± 35.8 msec, mean SD 411 ± 31.2 msec; p=0.04). The QTc interval decreased by 20.9 msec from baseline to 24 weeks (p=0.001) following TCZ treatment. QTc interval prolongation at baseline was significantly correlated with the anticyclic citrullinated peptide antibody (ACPA) at baseline (p=0.003). ACPA at baseline (p=0.001) was associated with %change in QTc interval. Furthermore, no significant associations between QTc interval and RA activity were observed. Conclusions: Tocilizmab treatment in patients with RA decreases QTc interval. Furthermore, anti-arrhythmic potential of TCZ treatment may have beneficial effects in patients with RA. Our results provide further evidence regarding the close association between ACPA degree and QTc intervals. Disclosure of Interest: None declared